Fatty acid conjugation enhances potency of antisense oligonucleotides in muscle. Issue 12 (25th May 2019) - Prakash, Thazha P; Mullick, Adam E; Lee, Richard G; Yu, Jinghua; Yeh, Steve T; Low, Audrey; Chappell, Alfred E; Østergaard, Michael E; Murray, Sue; Gaus, Hans J; Swayze, Eric E; Seth, Punit P
Abstract: Enhancing the functional uptake of antisense oligonucleotide (ASO) in the muscle will be beneficial for developing ASO therapeutics targeting genes expressed in the muscle. We hypothesized that improving albumin binding will facilitate traversal of ASO from the blood compartment to the interstitium of the muscle tissues to enhance ASO functional uptake. We synthesized structurally diverse saturated and unsaturated fatty acid conjugated ASOs with a range of hydrophobicity. The binding affinity of ASO fatty acid conjugates to plasma proteins improved with fatty acid chain length and highest binding affinity was observed with ASO conjugates containing fatty acid chain length from 16 to 22 carbons. The degree of unsaturation or conformation of double bond appears to have no influence on protein binding or activity of ASO fatty acid conjugates. Activity of fatty acid ASO conjugates correlated with the affinity to albumin and the tightest albumin binder exhibited the highest activity improvement in muscle. Palmitic acid conjugation increases ASO plasma Cmax and improved delivery of ASO to interstitial space of mouse muscle. Conjugation of palmitic acid improved potency of DMPK, Cav3, CD36 and Malat-1 ASOs (3- to 7-fold) in mouse muscle. Our approach provides a foundation for developing more effective therapeutic ASOs for muscle disorders.